KAJIAN ESTETIKA RESEPSI PRODUKTIF KEKAFILAHAN NABI ADAM DALAM PUISI INDONESIA MODERN - Puji Santosa (Balai Bahasa Sulawesi Selatan, 2011)
This study aims to reveal and describe the productive reception the caravan of Adam in nine modern Indonesian poetry, the